Revolution in Cuba and Iran: Toward a Unified Theory of Analysis - Sims, Mason (AUC Knowledge Fountain, 2023)
This thesis seeks to fill a small gap in the study of revolution through unifying approaches and theories utilized to explain the complex social phenomenon. To facilitate this, a large portion of the work focuses on revolution literature which has been chosen to represent authors from the earliest generations covering the subject to the more recent. In compiling and reviewing these works, it can be seen that there exist common lines of not just explanation, but also a continuous series of critiques resurfacing within each generation. Within this compilation lies the roots of the theory presented in this thesis, that theory being an integrated conception of revolution can be constructed to form a solid basis of analysis for past and future revolutions. This theory is hypothesized through the argument that the greatest manifestation of favorable conditions and catalysts for revolution are a coalescence of alternative leaderships, effective ideologies, and drastic structural change. Further, this theory is tested through the arguably rare, if not novel comparison, between the Iranian and Cuban revolutions. The choice of these two movements is to demonstrate that an integrated theory is transferable between cases and able to cross temporal, cultural, geographic, and historical boundaries. Lastly, throughout the entirety of the case studies and in addition to the case selection itself, there is an effort made to demystify the confounding and often overgeneralized characterization of both movements with arguments presented that they are not inherently different from classic examples of revolution.